2022
DOI: 10.1111/jmwh.13320
|View full text |Cite
|
Sign up to set email alerts
|

Provider Characteristics Associated with Trust When Caring for Women Experiencing Substance Use Disorders in the Perinatal Period

Abstract: Introduction Women experiencing substance use disorders (SUD) have often reported challenges in their relationships with health care providers during the perinatal period that served as a barrier to care. Establishing trust is an important aspect in forming positive relationships. The purpose of this study was to identify provider characteristics associated with the development of trust when caring for women experiencing SUD during the perinatal period. Methods A systematic search was conducted using the datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Prior research suggests that barriers to entry into prenatal care among women using substances may include lack of transportation, mistrust of the medical system, and fear of stigma or legal implications (Frazer et al, 2019 ). These barriers highlight the importance of trauma-informed, supportive care from unbiased providers throughout the perinatal period (Renbarger et al, 2022 ). Strategies that promote comprehensive prenatal care, address barriers and concerns, and allow for honest communication about substance use with a trusted provider should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that barriers to entry into prenatal care among women using substances may include lack of transportation, mistrust of the medical system, and fear of stigma or legal implications (Frazer et al, 2019 ). These barriers highlight the importance of trauma-informed, supportive care from unbiased providers throughout the perinatal period (Renbarger et al, 2022 ). Strategies that promote comprehensive prenatal care, address barriers and concerns, and allow for honest communication about substance use with a trusted provider should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…24 APPs are well suited to treat patients with OUD given nursing and midwifery philosophies based on whole-person care that perfectly align with this work. Renbarger et al 25 determined, through systematic review, that pregnant patients with substance use disorders valued health care providers who demonstrated caring behaviors, included women in planning care, demonstrated competence specific to substance use treatment, and provided patient education, characteristics central to nursing and midwifery care.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,20 Additionally, there is inconsistency in professional practice to support breastfeeding in women on OMT. 14,16,21 Current understanding of the barriers to breastfeeding among women on OMT does not fully explain the gap between intention to breastfeed and actual practice. Yonke et al reported low breastfeeding incidence among women on OMT at hospital discharge and at 2-month follow-up, even though 92% of the cohort stated their intention to breastfeed prenatally while in treatment, receiving prenatal care, and delivering in a hospital that actively supported breastfeeding.…”
mentioning
confidence: 99%
“…Clinicians and scholars recognize that women on OMT may experience barriers to breastfeeding beyond those of the general population 11-13. Several studies have found factors that prevent successful breastfeeding in women on OMT, including inaccurate information, misconceptions, and lack of support from providers and nurses 14-16. Other studies describe social factors that impact a woman’s self-confidence in breastfeeding, such as stigma against addiction and breastfeeding, fears and anxieties about the newborn’s health, and a lack of support from family and friends 11,17.…”
mentioning
confidence: 99%
See 1 more Smart Citation